Megacity Seoul : urbanization and the development of modern south - Joo,Yu-Min (Routledge Advances in Korean Studies, 2019)
In Asia, there are a growing number of gigantic megacities, accompanied by a series of speculative and extravagant megaprojects. Amid the fast-paced urban and development challenges, many Asian governments have been searching for replicable and inspirational cases in Asia. South Korea and its capital city, Seoul, are among frequently referenced models. However, South Korea’s "economic miracle" in the late twentieth century has been mostly studied through an economic policy lens. This book revisits the development of South Korea by looking at its urban dimension and exploring the city of Seoul as a developmental megaproject